Mid-Term Project Workshop (Deliverable D12) - Pina, António Manuel Silva (2008)
This document is intended to provide a report of the Mid-Term Project Workshop. The Conference was fully integrated within the 2nd Iberian Grid Infrastructure Conference, held in Oporto on 12th – 14th May, 2008, at FEUP, Faculdade de Engenharia de Universidade de Porto.